The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1021/ja960642f
|View full text |Cite
|
Sign up to set email alerts
|

A New Catalyst for a Pd Catalyzed Alder Ene Reaction. A Total Synthesis of (+)-Cassiol

Abstract: The scope of the palladium catalyzed cycloisomerization of enynes in an Alder ene type fashion that led to a new catalytic system was explored in the context of a synthetic strategy to the antiulcerogenic agent (+)-cassiol. In a model study, the effect of six-membered ring formation, the presence of a carbonyl group in the tether, and the steric hindrance of the alkene conspire to prevent the cycloisomerization under the "standard" conditions. Two variables proved key in the development of a new catalytic syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…[9a] Many useful variants of this type of process, including asymmetric ones, followed thereafter, [10] as did the discovery and application of homologous processes employing 1,7-enynes as substrates. [11] Interestingly, in those substrates lacking a hydrogen-bearing substituent at the 'outer' allylic position or where there is branching at C3, the isomerisation reaction often yields 1,3-dienes. This is exemplified by the conversion of the 1,6-enyne 3 into the isomer 4 (Scheme 2) when N,N-bis-(benzylidene)ethylenediamine (BBEDA) is used as ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9a] Many useful variants of this type of process, including asymmetric ones, followed thereafter, [10] as did the discovery and application of homologous processes employing 1,7-enynes as substrates. [11] Interestingly, in those substrates lacking a hydrogen-bearing substituent at the 'outer' allylic position or where there is branching at C3, the isomerisation reaction often yields 1,3-dienes. This is exemplified by the conversion of the 1,6-enyne 3 into the isomer 4 (Scheme 2) when N,N-bis-(benzylidene)ethylenediamine (BBEDA) is used as ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[9d] Elegant applications of such processes in natural products synthesis abound. [7,[10][11][12][13] Since the original discovery of Trost and Lautens, [9] a range of other metal catalysts has been shown to effect the cycloisomerisations of 1,6-and 1,7-enynes and often in ways that are complementary to the processes observed using palladium. So, for example, when 1,6-enyne 5 (Scheme 3) is treated under 'conventional' conditions with (Ph 3 P) 2 Pd(OAc) 2 then the 1,3-diene 6 is formed [12] while reaction of the same substrate with the cationic ruthenium catalyst CpRu(MeCN) 3 þ PF 6 affords the isomeric 1,4diene 7 in a completely regio-and stereo-selective manner.…”
Section: Introductionmentioning
confidence: 99%
“…Under "ligandless" conditions, the cyclization of alkynyl ketone 20 proceeds in high yield (Scheme 5). 18 Another benefit to transition metal catalysis is the opportunity to intercept reaction intermediates for further transformations. Iterative trapping of the σ-palladium species derived from the initial carbometallation event in the Alder-ene process with tethered olefins allows for tandem cycloisomerizations.…”
mentioning
confidence: 99%
“…By two successive alkylations of 16 with methyl iodide and with 3,3-dimethoxypropyl iodide (17) respectively, the ester 18, with the required stereochemistry at the quaternary stereocenter, was obtained in excellent yield.…”
Section: Strategies Based On the Assembly Of A Chiral Cyclohexenone/cmentioning
confidence: 99%
“…Also in 1996, based on the strategy outlined retrosynthetically in Scheme 16, Trost et al 17 reported a new total synthesis of (+)-cassiol (2). The key features of Trost's cassiol synthesis are the new palladium catalyzed cycloisomerization of enyne 66 in an ene type fashion to the cyclohexanone derivative 65, the elaboration of the side chain present in cassiol by a palladium (0) catalyzed reaction (68 → 67) and the generation of the quaternary carbon stereocenter by an enzymatic process.…”
Section: The Palladium Catalyzed Cycloisomerization Strategymentioning
confidence: 99%